The Effect of Capillary Tube Length & Diameter on Compressor Performance of Refrigeration System - Adam E. Mohammed; Waled Y. Bouhawish; Majdi A. Razig (African Journal of Advanced Pure and Applied Sciences, 2024)
As the name suggests, the compressor is a device that compresses and raises the pressure of the refrigerant vapor coming from the evaporator, resulting in a saturation level that is higher than that of the chilled medium. As a result, the compressor needs to be powered by the actuator or main engine. The compressor can be referred to as a heat pump since it transfers heat from a low-temperature medium (the evaporator) to a high-temperature medium (the condenser). To determine how the capillary tube’s width and length affected the compressor’s performance in the refrigeration system, a basic refrigeration system was put together and used in this study. Three distinct lengths of capillary tubes were used, which are ((3m, 2m, 1m)) and two different diameters, which are (2.0mm, 2.2mm). Among the results obtained, the best performance coefficient and equivalent to the size of the compressor used were achieved when using the length ((1m)) and diameter ((2.0mm)) for the capillary tube, where the performance coefficient was ((6.8)).